Unique structures of organelles observed in primary spermatocytes after micro‐injection of protein solutions such as immunoglobulin into the lumen of the seminiferous tubules in mice and rats. (1st November 2012) - Toyama, Y.; Chen, C.; Yamatoya, K.; Maekawa, M.; Ito, C.; Toshimori, K.
Summary: Unique membranous structures of intracytoplasmic organelle, sting of a stack of a few flat cisternae about 50 nm in thickness, were found in mouse and rat spermatocytes after micro‐injection of immunoglobulin G into the lumina of the seminiferous tubules. Other proteins such as BSA and cytochrome c used in this study also induced the structures. In most cases, the stacks of cisternae were rolled up like cigars or cylinders. The structures varied in length and diameter, the largest one observed in this study being 10.7 μm in length. The structures did not appear when the testes were fixed just after micro‐injection and were formed transiently: they were observed in the spermatocytes fixed between 1 and 4 h after injection. Cytochrome c, micro‐injected as an inter‐cellular tracer, was visualised by a diaminobenzidine reaction. As the reaction product was not contained in the cisternae of the unique structures, the lumen of the cisternae of the organelles was not continuous with the inter‐cellular space. A flocculent material of low density was observed in the cisternae of the organelle. Similar material was observed in the lumina of solitary cisternae of the rough endoplasmic reticulum in the spermatocytes, suggesting that the structures derived from endoplasmic reticulum.